Perilla frutescens leaves extract ameliorates ultraviolet radiation-induced extracellular matrix damage in human dermal fibroblasts and hairless mice skin. (4th January 2017) - Bae, Jung-Soo; Han, Mira; Shin, Hee Soon; Kim, Min-Kyoung; Shin, Chang-Yup; Lee, Dong Hun; Chung, Jin Ho
Abstract: Ethnopharmacological relevance: Perilla frutescens (L.) Britt. (Lamiaceae) is a traditional herb that is consumed in East Asian countries as a traditional medicine. This traditional herb has been documented for centuries to treat various diseases such as depression, allergies, inflammation and asthma. However, the effect of Perilla frutescens on skin has not been characterized well. Aim of the study: The present study aimed to investigate the effect of Perilla frutescens leaves extract (PLE) on ultraviolet radiation-induced extracellular matrix damage in human dermal fibroblasts and hairless mice skin. Materials and methods: Human dermal fibroblasts and Skh-1 hairless mice were irradiated with UV and treated with PLE. Protein and mRNA levels of various target molecules were analyzed by western blotting and quantitative RT-PCR, respectively. Histological changes of mouse skin were analyzed by H&E staining. To elucidate underlying mechanism of PLE, activator protein-1 (AP-1) DNA binding assay and the measurement of reactive oxygen species (ROS) were performed. Results: PLE significantly inhibited basal and UV-induced MMP-1 and MMP-3 expression dose-dependently, and also decreased UV-induced phosphorylation of extracellular signal-regulated kinases and c-Jun N-terminal kinases. This inhibitory effects of PLE on MMP-1 and MMP-3 were mediated by reduction of ROS generation and AP-1 DNA binding activity induced by UV. Furthermore, PLE promoted type I procollagen production irrespective of UV irradiation. In the UV-irradiated animal model, PLE significantly reduced epidermal skin thickness and MMP-13 expression induced by UV. Conclusion: Our results demonstrate that PLE has the protective effect against UV-induced dermal matrix damage. Therefore, we suggest that PLE can be a potential agent for prevention of skin aging. Graphical abstract: